Comparison of remaining coal-burning ash-based on Cd, Pb, and Hg concentration at different temperatures: a case study in Aceh province - Asri, Gani; Erdiwansyah, Erdiwansyah; Sardjono, R. E.; Mariana, Mariana; Rizalman, Mamat (Vilnius Gediminas Technical University, 2022)
This study aims to investigate the efficiency level of absorption of heavy metals Cd, Pb, and Hg. Combustion is carried out using coal with the addition of absorbent ratios of 2%, 4%, 6%, 8%, and 10%. The adsorbent used is natural zeolite which is widely available and inexpensive. This study provides practical implications for the easy and inexpensive removal of heavy metal emissions during combustion. The results show that the maximum efficiency level for Cd metal reached 22.96% which was recorded at a temperature of 600 °C for an adsorbent ratio of 10%. The maximum efficiency level of Pb metal from the experimental results was obtained at a temperature of 600 °C with an adsorbent ratio of 10% to 10.83%. Meanwhile, the efficiency level for Hg metal produced was 0.05% which was recorded at the adsorbent ratio of 10% at 800 °C. The maximum total capacity of Pb metal for each tested combustion temperature was 600 °C 39.85 mg/kg, 700 °C 25.43 mg/kg, and 800 °C 7.21 mg/kg. On the other words, the higher the combustion temperature tested, the lower the absorption efficiency rate obtained.